TEORI DAN PRAKTEK EQUIVALENSI DALAM PENERJEMAHAN ENGLISH-INDONESIA - Gaguk Rudianto; Yunisa Oktavia (IdeBahasa, 2021)
Translation does not only translate from the source language (ST) to the target language (TT) because if it is done, the translation results or (TT) will not be accepted by the target language user and will not have the same effect as the source language. This is called the concept of equivalence. Equivalence is a problem that can not only be accepted by users of the target language which is also in accordance with the context of the culture, customs and habits of the local community, but this concept is essentially the result of the translated text having the same impact between the source language and the target language. This article analyzed the concept of theoretical and practical equivalence of translation from English to Indonesian or vice versa. The purpose of writing this article is to reveal the equivalence of translation and at the same time reveal translation errors that often occur in society. The data collection method used in this article is SBLC or free-to-talk (Sudaryanto, 1993). While the data analysis method is equivalent which was also written by the same expert.